The Effectiveness of Learning using the Case Method in Building Construction Drawing Courses - Gusmareta, Yuwalitas; Prima, Fani Keprila; Yandra, Muvi; Agammuddin, Agri Americo; Zola, Prima (CIVED, 2024)
College tall is one of the essential pillars in shaping the future generation, the successors of our nation. They must be capable of thinking quickly and precisely to tackle every problem and challenge in life. As challenges, demands, and competition, particularly in the world of work, continue to escalate, it becomes increasingly crucial for individuals to adapt their learning methods to keep pace with current curricula and developments. One of the latest advancements in the realm of education, especially in higher education, is the implementation of the Independent Campus Learning (MBKM) curriculum. MBKM represents a significant breakthrough, and all students studying at universities must adapt to it. In the Building Engineering Education Study Program at FT-UNP Civil Engineering Department, subjects like Building Drawing Construction are offered, focusing on developing essential skills. This subject covers a range of materials, from understanding soil characteristics for building foundations to drawing construction plans for various building components. Through methods like action research, students engage in three cycles of study, involving planning, implementation, observation, and reflection. Research conducted on Semester IV students in the 2021/2022 Academic Year at Padang State University revealed significant improvements in student performance. In Cycle I, the class average score was 72.3, with subsequent cycles showing steady progress, reaching an average score of 81.15 in Cycle III. These results demonstrate the effectiveness of the action-based learning approach in enhancing students' understanding and performance in Building Drawing Construction. It underscores the importance of dynamic teaching methodologies in preparing students for the challenges of the future workforce. With continued refinement and adaptation, initiatives like MBKM can play a pivotal role in shaping a skilled and competent workforce for tomorrow's society.